DETERMINING MARKETING STRATEGIES BASED ON FARMERS' BEHAVIOR TO INCREASE FARMERSâ WILLINGNESS TO BUY NITYAâS FEED PRODUCT - Anindhita Shafira Putri, Nadya
The main feed for cattle is forage, while concentrate is only an additional feed. However, currently forage is very difficult to obtain by cattle farmers. In addition, the condition of the quality of concentrate that is not fixed with high prices is also experienced by cattle farmers. Whereas the health of the cattle depends on the feed it consumes. Therefore, Nitya is here to bring innovation to cattle feed by producing an all-in-one feed containing forage in the form of seaweed as an alternative and concentrate in one package. Unfortunately, Nitya is still having trouble in determining the right marketing strategy. Therefore, this study aims to determine the factors that most influence cattle farmers in choosing cattle feed and provide recommendations for marketing strategies based on these factors. This research was conducted using a qualitative method through semi-structured interviews with 7 cattle farmers who have at least 20 beef cattle domiciled in a suburban area in West Java and analyzed using manual and selective coding methods. The results showed that the social environment of farmers greatly influenced cattle farmers in choosing cattle feed. Cattle farmers are very interested in cattle feed products that can fulfill cattle nutrition and are proven to be able to fatten their cattle. In addition, cattle farmers like to buy feed directly where they can reach, this is related to feed quality and feed prices. These findings can be helpful for developing a marketing strategy for Nitya. Keywords: Cattle, Concentrated Feed, Forage Feed, Cattle Feed, and Cattle Farmer